A Review of Current Research and Future Directions in Palliative Care and Death Education in Nursing Education - Zuo, Zhenzhen; Qian, Xiquan (Journal of Research in Vocational Education, 2025)
This study examines nursing students' palliative care competencies, attitudes toward death, and the current state of palliative care curriculum design. Educational interventions, such as participatory teaching and Noddings’ care theory, significantly enhance students’ skills and attitudes but require further exploration of their long-term effects and cultural relevance. Factors like empathy and social service experience influence students' willingness to engage in palliative care. Future research should focus on optimizing curricula, developing tailored evaluation tools, and investigating sustained impacts to improve nursing education and care for terminally ill patients.